“Everyone Has a Role in This”: Evaluating Organizational Readiness for a Digital Solution to Support Hypertension Care Teams and Patients - Canfield, Shannon M.; Rolbiecki, Abigail J.; Ghosh, Parijat; Martinez, William; Shaffer, Victoria A.; Montgomery, Emma E.; Dorr, David A.; Koopman, Richelle J. (Applied Clinical Informatics, 2025)
Hypertension is a significant contributor to cardiovascular disease, yet evidence-based blood pressure (BP) control practices are inconsistently applied. The Collaboration Oriented Approach to Controlling High Blood Pressure (COACH) is a digital clinical decision support tool designed to improve BP self-management and support clinician workflows. While the patient perspective on COACH has been evaluated in a separate study, this study evaluates organizational readiness for COACH implementation across three health systems using the Consolidated Framework for Implementation Research (CFIR).This study aimed to assess preimplementation facilitators and barriers for COACH, focusing on organizational readiness and modifiable factors influencing scalability.Qualitative interviews were conducted with 72 care team members from nine primary care clinics across three health systems using Epic or Oracle electronic health records. Data were analyzed using CFIR domains: innovation, inner setting, outer setting, individuals, and implementation process. Subdomains were rated from −2 (barrier) to +2 (facilitator).Overall, 79% of CFIR domain scores were positive, suggesting strong readiness for COACH implementation. The innovation domain scored 80% positive, highlighting COACH's user-friendly design, robust evidence base, and perceived advantages over current workflows. The inner setting domain showed 85% positive scores, driven by strong leadership, established infrastructures for patient-centered care, and high motivation for quality improvement. The outer setting domain scored 70% positive, reflecting barriers such as reimbursement policies, resource limitations, and staffing shortages. Participants noted the importance of continued leadership engagement, team-based support, and addressing workload challenges for sustainable implementation.The study demonstrates high organizational readiness for COACH, with critical barriers in reimbursement and resources that must be addressed for successful adoption. Findings underscore COACH's potential to enhance clinical decision-making and patient engagement. Future research should explore long-term impacts on care delivery and outcomes, informing broader adoption of digital health interventions in clinical practice.
Keywords: hypertension; clinical decision support systems; implementation science; electronic health records; health disparities